(untitled) (Research, Society and Development, 2021)
The prior objective of this work is to identify the awareness about the importance of using individual protection equiment (IPE) when handling/applying agrochemical and the actual use of IPE by farmers in the far west region of Santa Catarina in their chores. For data collection, a questionnaire was conducted with the families of students from the technical course in Agriculture at the Rural Family House of São José do Cedro - SC and covered the municipalities of São José do Cedro, Princesa, Guarujá do Sul, Dionísio Cerqueira and Anchieta, all belonging to the extreme western region of Santa Catarina. In order to analyze the gathered data, Microsoft Excel spreadsheets were used to create graphs so that the data found could be better visualized. It can be observed that most families know the importance of using IPE when working on their activities using agrochemicals, however, most still dispensing the use of such equipment either completely (not using it at any stage) or partially (using in some stages of the activities). Most of them claim that it is uncomfortable to wear this type of protection because it generates a feeling of warmth for the user. These facts become worrying due to the risks of manipulating such dangerous substances in these activities without using IPE.